Numerical investigation of the cavity shedding mechanism in a Venturi reactor. (August 2020) - Fang, Liang; Li, Wei; Li, Qiang; Wang, Zhenbo
Highlights: The separation of cavity and wall is the essence of re-entrant jet induced shedding The sign of re-entrant jet induced shedding is the axial fracture of the whole cavity The damage of the cavity is the essence of the bubbly shock shedding The sign of bubbly shock shedding is the circumferential defects and fractures The effect of bubbly shock is weakened with the decrease of pressure ratio Abstract: The shedding mechanism is a hot topic in cavitation research, and the shedding mechanisms induced by the re-entrant jet and bubbly shock, respectively, have been long studied and debated. In this study, based on experimental research, a numerical investigation of a Venturi reactor is performed using a self-developed compressible cavitation phase-change solver in order to determine the shedding mechanism. Through the quasi-periodic evolution of the cavity, combined with the contour of streamwise velocity and pressure, the main characteristics and physical signs of the re-entrant jet and bubbly shock mechanisms are studied. The effect of the pressure ratio on the shedding mechanism is also studied. It was found that, in a Venturi reactor with a long throat, the evolution of cavitation is divided into an inception stage, a development stage, two shedding stages, and a collapse stage. The main characteristic of the shedding mechanism induced by the re-entrant jet is the separation between the cavity and the wall. The physical sign of this type of shedding is the axial fracture of the whole cavity. Shedding induced by the re-entrant jet dominates the first shedding in the diffusion section. The main characteristic of the bubbly shock shedding mechanism is damage to the cavity caused by pressure waves or shocks, which accelerates cavity shedding and restrains cavity development. The physical sign of this type of shedding is circumferential defects and fractures in the cavity. The second shedding is jointly caused by the re-entrant jet and bubbly shock. The second shedding cavity may collapse rapidly or merge with the newly formed cavity, which can damage or strengthen the newly formed cavity, respectively. With the decrease of the pressure ratio, the effect of the bubbly shock shedding mechanism is weakened.